Pengaruh Literasi Keuangan dan Penggunaan E-Wallet Terhadap Sikap Keuangan Dikalangan Mahasiswa Fakultas Ekonomi UKRI (Lembaga Pengembangan Kinerja Dosen, 2025)
This study was conducted to examine the influence of financial literacy and e-wallet usage on the attitudes of students of the Faculty of Economics, National University of the Republic of Indonesia (UKRI). The background of this study is the rapid growth of e-wallet usage among the younger generation, especially generation Z, which is not always accompanied by adequate financial literacy skills. This study uses a quantitative approach with a survey method by distributing questionnaires to 90 student respondents. Data assistance analysis was carried out using multiple linear regression with SPSS software version 25. The results of the study show that partially, both financial literacy and e-wallet usage have a positive and significant effect on students' financial attitudes. Simultaneously, both variables also have a significant effect with a coefficient of determination (Adjusted R²) of 39.5%, which indicates that financial literacy and e-wallet usage together are able to explain the financial attitude variable by 39.5%. This finding emphasizes the importance of strengthening financial literacy and utilizing financial technology wisely to form more positive financial attitudes among students.